Only lovers left alive [videorecording (DVD)] - Jarmusch, Jim, 1953-; Swinton, Tilda; Wasikowska, Mia, 1989-; Hiddleston, Tom (Sony Pictures Classics, 2014)
Set against the romantic desolation of Detroit and Tangier, an underground musician, deeply depressed by the direction of human activities, reunites with his resilient and enigmatic lover. Their love story has already endured several centuries at least, but their debauched idyll is soon disrupted by her wild and uncontrollable younger sister. Can these wise but fragile outsiders continue to survive as the modern world collapses around them?